Penanaman Nilai-Nilai Karakter Terhadap Peserta Didik Sekolah Dasar Melalui Permainan Tradisional Congklak Atau Lumbung - Dewi Nurhasanah Nasution; Daulat Saragi; Yakobus Ndona (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Traditional games are games passed down from ancestors, but traditional games have been marginalized because in the modern era 4.0 the use of technology is very much used in everyday life. The technology that is often used is cellphones. The use of cellphones starts from teenagers, adults and even children who use cellphones like elementary school children. Mobile phones are usually used by children to play online games because children can play online games anywhere and anytime, which results in children not playing with their peers because they are already engrossed and focused on the online games on their mobile phones. This research aims to explore the character values ​​that can be instilled in elementary school students through game congklak or barn. This research uses a qualitative method with a literature review. The results of this research show that the traditional game congklak or lumbung can instill character values ​​in elementary school students such as the values ​​of honesty, discipline, hard work, creativity, curiosity, independence, communicativeness, responsibility and respect for achievement.